2005
DOI: 10.1080/09687860500063340
|View full text |Cite
|
Sign up to set email alerts
|

The α7 nicotinic acetylcholine receptor: Molecular modelling, electrostatics, and energetics

Abstract: The structure of a homopentameric alpha7 nicotinic acetylcholine receptor is modelled by combining structural information from two sources: the X-ray structure of a water soluble acetylcholine binding protein from Lymnea stagnalis, and the electron microscopy derived structure of the transmembrane domain of the Torpedo nicotinic receptor. The alpha7 nicotinic receptor model is generated by simultaneously optimising: (i) chain connectivity, (ii) avoidance of stereochemically unfavourable contacts, and (iii) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 68 publications
1
25
0
Order By: Relevance
“…The authors reported an energy profile similar to ours (see Fig. 6 of [4]): the energy decreased as the ion entered the protein, then rose in the middle of the extracellular domain, and dropped to a global minimum near the junction of the extracellular and transmembrane domains. The interaction energy remained high throughout the transmembrane domain, as in our results.…”
Section: Ionic Passage Through the Channelmentioning
confidence: 54%
See 1 more Smart Citation
“…The authors reported an energy profile similar to ours (see Fig. 6 of [4]): the energy decreased as the ion entered the protein, then rose in the middle of the extracellular domain, and dropped to a global minimum near the junction of the extracellular and transmembrane domains. The interaction energy remained high throughout the transmembrane domain, as in our results.…”
Section: Ionic Passage Through the Channelmentioning
confidence: 54%
“…First, the large extracellular domain carries the recognition sites for both the natural agonist GABA and the clinically important benzodiazepines [3,27,96]. Secondly, the transmembrane domain forms the ion channel and contains the channel gate [4], in addition to an intra-helical hydrophobic pocket that is important for the interaction of these receptors with intravenous and volatile anaesthetics [39]. Finally, the intracellular domain contains portals through which ions access www.elsevier.com/locate/JMGM Journal of Molecular Graphics and Modelling 26 (2007) [760][761][762][763][764][765][766][767][768][769][770][771][772][773][774] the cell cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the important structural homology and sequence similarity (24% identity), between the AChBP and the ligand binding domain of neuronal ␣7, homology modeling can offer a useful tool to investigate ligand binding. The structure of the chicken ␣7 homopentamer has been constructed based on both the X-ray structure of the L. stagnalis AChBP and the electron microscopy-derived structure of the transmembrane region of the T. marmorata nicotinic receptor (Amiri et al, 2005). Le Novère et al (2002) built a three-dimensional model of the N-terminal domain of a homopentameric chicken ␣7 nAChR based on AChBP, which was then used to analyze the docking of ACh, epibatidine, and nicotine (Le Novère et al, 2002).…”
mentioning
confidence: 99%
“…The muscle AChR models show a different shape and conformation of the channel gate if compared to previous studies based on human AChRs. Most of the previous studies (18)(19)(20)(21)(22)(23) have revealed the presence of a hydrophobic gate of Val and leu residues located in the mid-TM region, such ring representing the most constricted region of the whole channel.…”
Section: Pore Radiusmentioning
confidence: 99%